L’activité d’arboriste-élagueur en milieu urbain : la sécurité en action comme structurante pour le travail dans les arbres - Anne-Cécile Lafeuillade; Adelaide Nascimento (Perspectives Interdisciplinaires sur le Travail et la Santé)
This paper explores how arborists incorporate safety management in their work activity. Data-gathering was based on both the observation of pruning sites and the auto- and allo-confrontation method in which four arborists commented 3 videos of pruning situations that they or their colleagues had directed. The results show the conflict that arises between efficient production and risk prevention strategies. Harmonious cutting requires tree cultivation know-how, but also the proper control of one’s movements in the tree when hanging from ropes. This control is intimately linked to the management of both risk and efficiency, particularly with regard to reducing pain and fatigue. Based on these results, we demonstrate that safety management is an integral dimension of tree work, permitting both the effective use of equipment and tools – including one’s own body – and efficient care for trees.